Does Learning About Near-Death Experiences Promote Psycho-Spiritual Benefits in Those Who Have Not Had a Near-Death Experience? - Tassell-Matamua, Natasha (Journal of spirituality in mental health, 2017)
Research has revealed a consistent pattern of positive aftereffects in those who report a near-death experience [NDE]. Beneficial outcomes are also possible for those who have not had a NDE, but instead learn about them, although much of this research has been conducted on therapeutic populations. Using a sample of 143 participants randomly assigned to either an intervention or non-intervention group, we investigated whether learning about NDEs generated the same psycho-spiritual benefits having a NDE does. Results revealed significant changes in appreciation for life, spirituality, and appreciation for death, in the intervention group after learning about NDEs.